COST TU1406 – An overview of European Standardization on Quality Control of Road Bridges - Matos, José C. (2017)
Road asset management is a task of great responsibility, since it involves vital assets to the community. An efficient transportation network is essential for the modern society from the economic, societal and environmental point of view. Today, it is a challenge for operators to manage road infrastructures under their responsibility in an efficient way, meeting the present and future needs of the community they serve. For this purpose, authorities need to produce an asset management plan which should not only define the goals to be achieved by exploiting the roadway bridge network, but should also identify investment needs and priorities based on a life cycle cost criteria. In addition, a proper condition assessment of these assets must be conducted to support the decision-making process regarding their preservation. COST Action TU1406 aims to quantify performance indicators, define standardized performance goals and develop a guideline to establish quality control plans at a European level.